El discurso del Poder Popular en Venezuela: Mitos y realidades de la Revolución Bolivariana de Hugo Chávez - García Chourio, José Guillermo (Diálogos Latinoamericanos, 2011)
The discourse of class struggle that has been attributed to the revolutionary Venezuelan process is an insufficient sample to be able to understand the political identities and alteration arisen during this evolution. Considering the orientation of the left-wing presented by the regime, this work analyzes the speech of the "popular power" of the so called Bolivarian Revolution, putting emphasis on the new logics and dynamics of integration and social and political exclusion that have been generated during the governments of Hugo Chávez, as much in the symbolic level as on the material level. This revolutionary speech of the popular power has been employed, beyond any socialist ideological paradigm, to support the building of social differentiation patterns between the people, which have created a worrying state of political and social intolerance. This context has been reinforced by the restrictions produced by state-citizen relationship where the intermediation through political clientelism and populism gives privileges principally to those persons loyal to the project of revolution.